Screening of chilli pepper genotypes against anthracnose (Colletotrichum brevisporum) - Silva Souza, Leonor Cristina; Guimarães Assis, Luiz Alberto; Catarino, Aricléia de Moraes; Hanada, Rogério Eiji (Emirates Journal of Food and Agriculture, 2020)
Anthracnose is the most important disease of chili pepper pimenta-de-cheiro (Capsicum chinense Jacq.). This species is widely cultivated in dryland areas in the Amazon, presenting high genetic diversity. Therefore, it presents a high potential for use in breeding. The objective of this study was to select pepper genotypes with potential resistance to anthracnose (Colletotrichum brevisporum). For this purpose, ripe fruits of pepper were acquired from the producing farms in the municipalities of Iranduba, Manacapuru, Rio Preto da Eva and Presidente Figueiredo. The experiments were conducted in seedlings (Phase I) and in mature and immature fruits (Phase II). The evaluation of the disease severity was performed using a scale of scores. The morphoagronomic characterization of the genotypes considered the fruits in the immature and mature stages and plant growth habit. The injured areas in the immature fruits ranged from 0.3 to 9.7 cm2 and in the mature areas, it ranged from 0.2 to 9.9 cm2. The genotypes RPE41 and MPU29 indicated resistance to anthracnose in both stages. The morphoagronomic characterization of the fruits revealed variability for mass (5.58 to 13.74 g), length [C] (4.08 to 8.16 cm), diameter [D] (1.74 to 2.54 cm), L/D ratio (1.88 to 4.70) and color of the fruit.